Database for women's empowerment indicators in Golfo de Fonseca, Honduras - Moreno, Manuel F.; Muriel, Juliana; Twyman, Jennifer; Wiegel, Jennifer Rebecca; Castro, Judith; Suazo, Carlos; Garcia, Maria Alejandra (2021)
This dataset contains relevant sex disaggregated data about gender roles, women's empowerment, and gender gaps in the production and processing nodes of three value chains: cashew, dairy and fruits in southern Honduras. The data was collected using an adapted version of the Women's Empowerment in Agricultural Index (WEAI) as part of the ‘Rural Market Opportunities' project implemented by Swisscontact and in partnership with the Alliance of Bioversity International and CIAT were initially used to inform the development of gender and social inclusion strategies for project interventions in agricultural value chains.